Climate Diplomacy as a Foreign Policy Tool: : Challenges and Prospects for Bangladesh - Ali, Ahamad; Afroze, Sanjida; Mahmud, Faysal (The Jahangirnagar Review, 2025)
‘Climate Diplomacy as a Foreign Policy Tool: Challenges and Prospects for Bangladesh’ explores how does Bangladesh utilize climate diplomacy to mitigate the adverse effects of climate change while advancing its foreign policy goals. As one of the world’s most climate-vulnerable area, Bangladesh faces lots of threat such as rising sea levels, cyclones, and resource insecurity. Through active engagement in global climate governance, this country seeks financial assistance, technological collaboration, and partnerships to enhance resilience and sustainable development. The study critically examines the opportunities and challenges associated with Bangladesh’s climate diplomacy. It highlights notable achievements, such as securing commitments on loss and damage financing at COP27, while addressing persistent barriers, including limited institutional capacity, overreliance on donor support, bureaucratic inefficiencies and geo-political tensions. Moreover, the new Interim Government lead by its Chief Advisor Professor Dr. Mohammad Yunus after the fall of Hasina government by the historic Monsoon Revolution on July-August 2024 has showed new dream to Bangladeshi people towards a new multi-lateral diplomacy with some barriers. These challenges hinder the effectiveness of Bangladesh’s climate diplomacy in securing international support for adaptation and mitigation initiatives.